BI Solution for Auditing SAP Outputs - Kalina, Martin; Maryška, Miloš; Sládek, Pavel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The objective of this thesis is to design and implement a Business Intelligence (BI) solution utilizing data from the SAP system to support auditing processes. The focus is primarily on the control of access rights and the monitoring of users' critical transactions. The introductory part of the thesis specifies the auditors’ requirements and defines the objectives of the audit testing. This is followed by an analysis of the data origin, their compatibility with different SAP versions, and an assessment of input data quality. The central part addresses the design of a single-layer BI architecture containing semi-structured preprocessing in Excel and subsequent processing in Power BI, using Power Query and DAX. The practical part verifies the functionality of the solution using real-world data and evaluates its benefits in terms of accuracy, time savings, and cost reduction within audit controls. The conclusion summarizes the results achieved, identifies shortcomings, and proposes possibilities for further development, particularly in the areas of automation and applicability in the implementation of ISO/IEC 27002, NIST CSF 2.0, or in meeting the requirements of the Czech draft Cybersecurity Act.
Vedoucí práce: Miloš Maryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: business intelligence [obor dipl. práce]; diplomové práce; master's theses